Uso da realidade aumentada e o QR CODE com o auxílio do aplicativo AR CIRCUITS 4D PHYSICS como recurso didático para o ensino de Física: Uma sequência didática para circuitos elétricos - COELHO, Pedro Henrique Lindoso (2023)
The great advance with the use of Information and Communication Technologies, along with the use of mobile devices among children and young people, is growing a lot in Brazil and especially in the classroom. Using QR code in classrooms can enhance classes and assist the teacher in many ways, including extending a topic that was taught in the classroom to any student-preferred environment using only QR code cards and a smartphone. This dissertation presents activities applied in the assembly of electrical circuits through the AR Circuits 4D physics application, along with QR code cards as a didactic resource for the improvement of Physics learning teaching. The educational theoretical basis of this work and applied meaningfully is David Ausubel's Theory of Meaningful Learning. About Educational Product developed in this work and accompanying this dissertation, was designed with the purpose of making it a Potentially Significant material and consists of the assembly of electrical circuits in the form of didactic sequence, using augmented reality with the use smartphone and the application that can be used by junior high school teachers to analyze and visualize through augmented reality, the electric current through circuit electrical devices, measuring electrical voltages, direct application of Ohm's law, electronics, magnetism, acoustics, optics and mechanics and manipulations of other electrical circuit elements . Circuit assemblies using QR code cards facilitate the teaching-learning process by stimulating student curiosity, arousing student interest in the content taught through the use of information and communication technology.